2009
DOI: 10.1186/1477-5956-7-17
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive proteomic analysis of human cervical-vaginal fluid using colposcopy samples

Abstract: Background: Cervical-vaginal fluid (CVF) plays an important role in the prevention of gynecological infections, although little is known about the contribution of CVF proteins to the immunity of the lower female genital tract. In order to analyze the protein composition of human CVF, we used CVF samples that are routinely collected during colposcopy, but are usually discarded. Since these samples are available in large quantities we aimed to analyze their usefulness for proteomics experiments. The samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
98
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 64 publications
8
98
0
1
Order By: Relevance
“…20 Our cytokine findings are consistent with previous studies that reported an increase of cervicovaginal pro-inflammatory cytokines in women with BV. 11,13,14 However, some cytokines that have frequently been studied in this context (such as IL-1b, IL-6, and IL-8) were not identified in our study, probably due to relatively low concentrations that fall outside the dynamic range of the mass spectrometer.…”
Section: Articlessupporting
confidence: 93%
See 1 more Smart Citation
“…20 Our cytokine findings are consistent with previous studies that reported an increase of cervicovaginal pro-inflammatory cytokines in women with BV. 11,13,14 However, some cytokines that have frequently been studied in this context (such as IL-1b, IL-6, and IL-8) were not identified in our study, probably due to relatively low concentrations that fall outside the dynamic range of the mass spectrometer.…”
Section: Articlessupporting
confidence: 93%
“…[9][10][11][12][13][14] Furthermore, in vitro studies have shown that lactobacilli do not generally induce human AMPs, whereas BV-associated bacteria (such as Gardnerella vaginalis, A. vaginae and P. bivia) do. 10,12 The cervicovaginal proteome has been characterized by others before, [15][16][17][18][19][20] but never in the context of different VMB compositions. We hypothesized that VMB dysbiosis is associated with cervicovaginal inflammation, and other changes to the mucosal barrier that might cause increased HIV acquisition and other adverse reproductive health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…This may explain why statistical significance was not observed in the validation cohort. FABP5 has been identified in the CVF by at least eight other groups but the existence of different isoforms could not be described using the technologies employed (Venkataraman et al 2005, Shaw et al 2007, Tang et al 2007, Klein et al 2008, Shah et al 2009, Zegels et al 2009). The significance of the different isoforms therefore remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The CVF proteome has been comprehensively characterised in pregnant and non-pregnant women , Di Quinzio et al 2007, Shaw et al 2007, Tang et al 2007, Klein et al 2008, Shah et al 2009, Zegels et al 2009, Heng et al 2010a. Using two-dimensional PAGE (2D-PAGE) proteomic analysis of human CVF, we have demonstrated temporal protein changes in association with impending spontaneous term labour (Di Quinzio et al 2008, Heng et al 2010a.…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies focused only on the particular proteins of interest. Recent advances in proteomic technologies have spurred several efforts toward the identification of the total protein repertoire of human reproductive tract fluids (Tsangaris et al 2006, Casado-Vela et al 2009, Zegels et al 2009, Jarkovska et al 2010. As a result, now there exists substantial information about the proteins, which collectively contribute toward creating extracellular microenvironments in vicinity of various reproductive tissues.…”
Section: Introductionmentioning
confidence: 99%